From the implantation of the charism to the franciscan province of the incarnate Word in West Africa : franciscanism and its future facing the challenges evangelization, fraternity and integral ecology - (:unkn) unknown (My University, 2022)
In 1956-57, two French Franciscan Provinces established missionary foundations in Togo and Ivory Coast. The first took charge of a region and set about implanting the Church, the second sought to implant the Order. Confronted with the same challenges and difficulties, they joined forces and founded in 2001 the Franciscan Province of the Incarnate Word, regrouping Benin, Burkina Faso, Ivory Coast, Ghana and Togo. In an interdisciplinary approach encompassing history, theology, ecclesiology, ethics and spirituality, the implantation of the Franciscan Order in this part of Africa, its evolution and the challenges with which the Franciscans are confronted, is examined. The contribution which African values have made to Franciscan spirituality make it possible to take up the contemporary challenges of interculturality and integral ecology. The missionary challenge consists in the reappropriation of the Franciscan charism in an African context facilitating in this way the mission inter and ad gentes.
Keywords: African Research